2019
DOI: 10.1007/s10750-019-04097-w
|View full text |Cite
|
Sign up to set email alerts
|

Insect-associated bacterial communities in an alpine stream

Abstract: The roles of macroinvertebrate and microbial communities in stream ecosystems are recognized to be important to energy flow and nutrient cycling. While the linkages of these major groups of aquatic organisms has not been thoroughly investigated, determining how they interact is particularly important for understanding the mechanisms and potential evolutionary relationships that contribute to ecosystem processes, such as organic matter decomposition. We evaluated the microbiomes of several aquatic macroinverteb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 70 publications
(104 reference statements)
3
22
2
Order By: Relevance
“…A Random Forest algorithm was used to identify the highest-ranking predictor taxa among timepoints using highest mean decrease gini scores. This analysis was performed using the randomForest R package using default parameters (1000 trees) [ 2 , 45 47 ]. This model works by determining how much a model decreases in accuracy by removing a certain taxon [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…A Random Forest algorithm was used to identify the highest-ranking predictor taxa among timepoints using highest mean decrease gini scores. This analysis was performed using the randomForest R package using default parameters (1000 trees) [ 2 , 45 47 ]. This model works by determining how much a model decreases in accuracy by removing a certain taxon [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…A summary of the most common bacterial phyla identified within the microbiota of terrestrial invertebrates (Colman et al, 2012;Hernández-García et al, 2017;Jones et al, 2013;Mikaelyan et al, 2015;Muturi et al, 2017;Pérez-Cobas et al, 2015;Rizzi et al, 2013;Singhal et al, 2017;Yun et al, 2014) and freshwater invertebrates (Ayayee et al, 2018;Pechal & Benbow, 2016;Receveur et al, 2020), fishes (Desai et al, 2012;X. Li et al, 2013;Roeselers et al, 2011;Sullam et al, 2012;Wu et al, 2012), plants (Srivastava et al, 2017;Tanaka et al, 2012), sediments (Zhang et al, 2019), bacterioplankton (Ayayee et al, 2018;Portillo et al, 2012), and biofilms (Ayayee et al, 2018) is shown in Table 7.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, environmental bacteria have shown differential growth across aquatic substrates (Goldfarb et al, 2011); thus, we are seeking to understand whether similar patterns exist within invertebrate microbiota sampled across different microhabitats within a sampling site. Given that previous studies of both terrestrial and aquatic invertebrates have revealed significant differences among diets or functional feeding groups (Ayayee et al, 2018;Colman et al, 2012;Jones et al, 2013;Kim et al, 2017;Knapp et al, 2009;Mikaelyan et al, 2015;Pechal & Benbow, 2016;Receveur et al, 2020;Xiang et al, 2019;Yun et al, 2014), this is a factor that will be investigated in the current study. Additionally, the methodological omission noted in previous aquatic invertebrate studies provides increased motivation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the high fine sediment deposition can alter the quantity of energy inputs, as it affects the amount of autotrophic production (Henley et al, 2000;Bona et al, 2016) and allochthonous coarse organic matter availability in Alpine streams (Doretto et al, 2016(Doretto et al, , 2017. In particular, the burial of leaf litter by sediments reduces availability of this resource and alters the composition of the microbial community involved in its degradation (Receveur et al, 2020), with consequent negative effects on shredder invertebrates (Danger et al, 2012).…”
Section: Effects Of Flow Intermittency On the Ecological Niches Of Nementioning
confidence: 99%
“…Therefore, as flow intermittency events occur in summer, they are expected to impact shredders during the oviposition and early instars, greatly reducing their survival and abundance, but also because recurrent drying events significantly alter organic matter processing, as already observed in Mediterranean streams (e.g., Abril et al, 2016). For instance, surface flow disappearance usually reduces the decomposition rate especially in dry streambed sediments, where the activity of Ingoldian fungi, bacteria and invertebrates are inhibited by emersion (Corti et al, 2011;Receveur et al, 2020). In addition, lower flow velocity reduces the removal of fine sediments, with consequent high fine sediment deposition, which can alter the quality and quantity of resources, in terms of both reduced instream production, due to the abrasion of autotrophic biofilms (Henley et al, 2000;Bona et al, 2016), and allochthonous coarse organic matter availability through burial (Doretto et al, 2016).…”
Section: Introductionmentioning
confidence: 99%